PERAN MEDIASI REPUTASI PERUSAHAAN TERHADAP HUBUNGAN ORIENTASI PASAR DAN CORPORATE SOCIAL RESPONSIBILITY DENGAN KINERJA BISNIS (Studi pada Industri Perbankan di Bali) - Rihayana, Gede (Buletin Studi Ekonomi, 2016)
The Mediating Role of Corporate Reputation on the Relationship between Market Orientation and CSR with Business Performance. This study aims to analyze the mediating role of corporate reputation on the relationship between market orientation and CSR with business performance, this study using questionnaires and interviews. Object of this study was the banking industry, both private banks and state banks in Bali. Prior to analysis to test the validity and reliability testing of the research instruments. Data were analyzed by Structural Equation Model (SEM) using SPSS software and smartPLS. The results of this study demonstrate, market orientation and CSR has a positive and significant relationship indirectly about business performance is mediated by a corporate reputation. Market orientation and CSR has a positive and significant relationship directly tehadap corporate reputation. Reputation of the company has a positive and significant relationship to business performance.   Keywords: market orientation, CSR, corporate reputation, bisnis performance
Keywords: market orientation, CSR, corporate reputation, bisnis performance